Sistem Pendukung Keputusan Dengan Metode Fuzzy Logic Untuk Menseleksi Mahasiswa Penerima Beasiswa - Arman, Arman (Jurnal EDik Informatika, 2015)
The decision in granting scholarships to students can use the Decision Support System (Decision Support System) by using certain methods, one using fuzzy logic and applied with the Microsoft Visual Basic programming language. Assessment with students who are entitled to receive can be done using several criteria, including the criteria of poverty or disability, criteria dependent parent, criteria value GPA of the semester, the criteria semester, students are being filed, and the criteria of activeness in the organization, especially student organizations on campus. Such criteria conducted with questionnaires, correspondence and interviews. Questionnaires given to each student who apply for a scholarship. Correspondence intended as Student Card, KHS, KK (family card), and other supporting certificate. Interviews were conducted with the questions asked by the parties to the Student Assessment. The assessment results entered into the fuzzy logic using the model Tahani. By determining the input and output variables are used. With the help of fuzzy logic, the decision in selecting scholarship recipients quickly, efficiently and effectively.